"BIM AND PLANT SYSTEMS: A SPECIFIC ASSESSMENT". (August 2018) - Marini, Martino; Mastino, Costantino C.; Baccoli, Roberto; Frattolillo, Andrea
Abstract: It is now known that the use of Building Information Modeling (BIM) procedures offers many benefits in the design and management of buildings. According to recent legislative enactments the BIM procedures will become mandatory for Public Works as from 2019. There are several advantages by using BIM procedures, among them the following can be highlighted: gaining a clear overview of the building plant system, evaluating the spatial coherence of the plant networks, the evaluation of the interferences to keep the system do not interfere with the functionality or the aesthetics of built environments. The present work analyzes the BIM procedures with particular reference to air conditioning systems in existing buildings, to their performance and management characteristics. The objective consists of analyzing the different BIM procedures and critically comparing the information provided by the IFC standard published by the European Institution Building SMART International, recognised as a standard by ISO, with the main reference standards for building installations and facilities design.